Effects of carbon monoxide on early dysfunction and microangiopathy following GalT‐KO porcine pulmonary xenotransplantation in cynomolgus monkeys. (25th October 2017) - Sahara, Hisashi; Sekijima, Mitsuhiro; Ariyoshi, Yuichi; Kawai, Akihiro; Miura, Kohei; Waki, Shiori; Nathan, Louras; Tomita, Yusuke; Iwanaga, Takehiro; Nakano, Kazuaki; Matsunari, Hitomi; Date, Hiroshi; et al.
Abstract: Background: Despite progress in the current genetic manipulation of donor pigs, most non‐human primates were lost within a day of receiving porcine lung transplants. We previously reported that carbon monoxide (CO) treatment improved pulmonary function in an allogeneic lung transplant (LTx) model using miniature swine. In this study, we evaluated whether the perioperative treatment with low‐dose inhalation of CO has beneficial effects on porcine lung xenografts in cynomolgus monkeys (cynos). Methods: Eight cynos received orthotopic left LTx using either α‐1, 3‐galactosyltransferase knockout (GalT‐KO; n = 2) or GalT‐KO with human decay accelerating factor (hDAF) (GalT‐KO/hDAF; n = 6) swine donors. These eight animals were divided into three groups. In Group 1 (n = 2), neither donor nor recipients received CO therapy. In Group 2 (n = 4), donors were treated with inhaled CO for 180‐minute. In Group 3 (n = 2), both donors and recipients were treated with CO (donor: 180‐minute; recipient: 360‐minute). Concentration of inhaled CO was adjusted based on measured levels of carboxyhemoglobin in the blood (15%‐20%). Results: Two recipients survived for 3 days; 75 hours (no‐CO) and 80 hours (CO in both the donor and the recipient), respectively. Histology showed less inflammatory cell infiltrates, intravascular thrombi, and hemorrhage in the 80‐hour survivor with the CO treatment than the 75‐hours non‐CO treatment. Anti–non‐Gal cytotoxicity levels did not affect the early loss of the grafts. Although CO treatment did not prolong overall xeno lung graft survival, the recipient/donor CO treatment helped to maintain platelet counts and inhibit TNF‐α and IL‐6 secretion at 2 hours after revascularization of grafts. In addition, lung xenografts that were received recipient/donor CO therapy demonstrated fewer macrophage and neutrophil infiltrates. Infiltrating macrophages as well as alveolar epithelial cells in the CO‐treated graft expressed heme oxygenase‐1. Conclusion: Although further investigation is required, CO treatment may provide a beneficial strategy for pulmonary xenografts.